The End of An Era? : The Medium- and Long-Term Effects of the Global Crisison Growth in Low-Income Countries - Papageorgiou, Chris (IMF Working Papers; Working Paper ;, 2010)
This paper investigates the medium- and long-term growth effects of the global financial crises on Low-Income Countries (LICs). Using several methodological approaches, including impulse response function analysis, growth spells techniques and panel regressions, we show that external demand (ED) shocks are not historically associated with sharp declines in output growth. Given existing evidence that LICs were primarily impacted by such a shock in the global financial crisis, our analysis provides some optimism on the chances that LICs will avoid a protracted period of slow growth. However, we also show that there seem to be persistent output losses associated with ED shocks in the medium-run. In terms of policy implications, our analysis provides evidence that countries with lower deficits, lower debt, more flexible exchange rate regimes, and a higher stock of international reserves are more likely to dampen the effects of an ED shock on growth.